(untitled) (International journal of artificial intelligence, 2025)
The state discusses the fact that microorganisms are one of the most important and widespread representatives of their nature and that they are of great importance not only in the processes of decomposition, but also in the muscular, medical, ecological and food spheres. In recent years, special attention in science and practice has been attracted by pigment-producing microorganisms, antioxidant and antibacterial pigments have the potential for wide application in pharmaceuticals.